Studies on Enhancement of Solubility Dissolution Rate and Bioavailability of Glipizide by Complexation with b-Cyclodextrin - Chowdary, K.P.R.; Raga, Sunil (Asian Journal of Chemistry, 2011)
The objective of the investigation is to study the complexation of glipizide, biopharmaceutical classification system class II drug with b-cyclodextrin (b-CD) and to evaluate the feasibility of enhancing its solubility, dissolution rate and bioavailability by b-cyclodextrin complexation. Complexation of glipizide with b-cyclodextrin was evaluated by phase solubility, TLC, DSC, XRD and IR spectral studies. Solid inclusion complexes of glipizide and b-cyclodextrin were prepared by kneading method and were evaluated by in vitro and in vivo methods. The aqueous solubility of glipizide was increased linearly as a function of concentration of the b-cyclodextrin. The phase solubility studies indicated the formation of glipizide-b-cyclodextrin inclusion complex at a 1:1 M ratio in solution. The complexes formed were quite stable. Solid inclusion complexes of glipizide-b-cyclodextrin exhibited higher rates of dissolution and dissolution efficiency values when compared to uncomplexed glipizide. Glipizide-b-cyclodextrin (1:3) complexes exhibited 5.58 fold increase in the dissolution rate and 4.76 fold increase in the dissolution efficiency of glipizide. TLC, DSC and IR spectral studies indicated no chemical interaction between the glipizide and b-cyclodextrin. XRD indicated stronger drug amorphization and entrapment of glipizide in b-cyclodextrin. All pharmacokinetic parameters estimated [Cmax, Tmax, Ka and (AUC)0¥] indicated rapid and higher absorption and bioavailability of glipizide when administered as b-cyclodextrin complex. The absorption rate constant (Ka) was increased from 2.08 h-1 for glipizide. (AUC)0¥ was increased from 86.2 μg h/mL for glipizide to 120.6 μg h/mL for b-cyclodextrin complex. Thus, complexation with b-cyclodextrin has markedly enhanced the absorption rate and bioavailability (both rate and extent of absorption) of glipizide, a biopharmaceutical classification system-class II drug.